A New Energy-Efficient Data Transmission Scheme Based on DSC and Virtual MIMO for Wireless Sensor Network - Na Li; Liwen Zhang; Bing Li (Journal of Control Science and Engineering)
Energy efficiency in wireless sensor network (WSN) is one of the primary performance parameters. For improving the energy efficiency of WSN, we introduce distributed source coding (DSC) and virtual multiple-input multiple-output (MIMO) into wireless sensor network and then propose a new data transmission scheme called DSC-MIMO. DSC-MIMO compresses the source data using distributed source coding before transmitting, which is different from the existing communication schemes. Data compression can reduce the length of the data and improve the energy efficiency. In addition, DSC-MIMO does not require the cluster heads to collect the data of the source nodes, which reduces the frequencies of data transmission and saves energy. In the simulation, we analyze the energy consumption of DSC-MIMO. The results indicate that DSC-MIMO can effectively reduce the energy consumption and improve the energy efficiency of the whole wireless sensor network.